2010
DOI: 10.1542/peds.2009-2204
|View full text |Cite
|
Sign up to set email alerts
|

An Adolescent With a Mediastinal Mass, Diagnosed With Graves Disease and Thymic Hyperplasia

Abstract: Graves disease is an autoimmune disorder characterized by thyroid enlargement and hyperthyroidism. Thyrotropin receptor (TSHR) autoantibodies bind the TSHR on the membrane of thyroid follicular cells and stimulate cell proliferation and thyroid-hormone synthesis. TSHR has also been identified in extrathyroidal organs, including the human thymus. Thus far, radiologically detectable thymic enlargement has only been reported in adults with Graves disease. We present here the case of a child with Graves disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…2). This latter finding was recently confirmed by Van der Weerd and collaborators [112]. The level of TSHR expression in thymocytes indicated that thymocytes are the major contributors to total thymic TSHR expression.…”
Section: Tshr In the Thymus And Its Possible Dual Role In Gd ▼mentioning
confidence: 52%
See 2 more Smart Citations
“…2). This latter finding was recently confirmed by Van der Weerd and collaborators [112]. The level of TSHR expression in thymocytes indicated that thymocytes are the major contributors to total thymic TSHR expression.…”
Section: Tshr In the Thymus And Its Possible Dual Role In Gd ▼mentioning
confidence: 52%
“…Do TSHR + thymocytes contribute to central tolerance failure in GD? The publication by de Weerd et al, demonstrated that TSHR expressed by thymocytes is functional, and TSH enhanced T-cell development in an in vitro co-culture system [112]. We have recently found that TSHR expression is confined to the developing T cells within the thymus (and not in the peripheral T cells) and strictly linked to the maturation process of thymocytes.…”
Section: Tshr In the Thymus And Its Possible Dual Role In Gd ▼mentioning
confidence: 91%
See 1 more Smart Citation
“…[9][10][11] Thyrotropin receptors are present in the thymus and, when stimulated by the anti-thyrotropin receptor antibodies present in Graves' disease, may result in thymic hyperplasia, 12 which has been described in pediatric Graves' disease. 13 In vivo data suggest an immunologic effect of antithyroid drugs such as methimazole. Use of an antithyroid drug…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five of these patients had a thymic mass that shrank under medical treatment for GD [9]. Thymectomy was performed in 11 patients and histology revealed: one case of reactive thymic hyperplasia [10]; two cases of thymic lymphoid hyperplasia with an increase in the number of lymphoid follicles revealing germinal centers largely composed of B lymphocytes (Mic2 and CD79a positive), and an increased content of Hassall's corpuscles showing keratin staining [11,12]; and one case of true thymic hyperplasia [12]. The limit of this review [9] lies in that it is only a collection of case reports and includes no large epidemiological studies, so the question of the real frequency of TH in GD remains unanswered.…”
Section: Review Of the Literaturementioning
confidence: 99%